A non-city? Nature in urban space and how to study it - Kaniowska, Katarzyna (A mosaic city: The culture-oriented description, 2023)
In any urban space there are those elements of it that have not been produced by man. In studies conducted by urban anthropologists, nature is rarely the subject of analysis. In the case of such research, we are faced with the question of what methodologies and what tools can be helpful and what dictionary of terms would be useful for describing and interpreting the nature present in the city. In this article, I consider the possible usefulness of two well-known concepts – those posed by Marc Augé and Ulf Hannerz, for the study of such fragments of urban spaces that completely belong to nature; they co-create the urban fabric, but bear witness to the interference of nature in the urban area.